Faktor yang Berhubungan dengan Keluhan Musculoskeletal Disorders pada Pekerja Batik Cap - Fitrianingrum, Defi (Jurnal Penelitian dan Pengembangan Kesehatan Masyarakat Indonesia, 2023)
Background: Musculoskeletal Disorders (MSDs) are soft tissue injuries caused by sudden or repetitive meovement, forces, vibrations, and awkward positions. Batik cap workers are at risk of developling musculoskeletal complaints because they work in a static position for a long time. The purpose of this study was determine the factors associated with the incidence of musculoskeletal complaints stamped batik workers. Method: This type of research is descriptive quantitative with a cross sectional approach using a total sampling method that is a number of 53 workers, the instruments used are measuring sheets observations and questionares. Data were analyzed using the chi-square test and fisher’s test. The research wa conducted in November-December 2022. Results: The conclution in this study is that the variables associated with musculoskeletal complaints were work posture (p=0.000), length of work (p=0.043), length of service (p=0.000), workload (p=0.019), age (p= 0.000). There was no relationship with the incidence of gender complaints (p=0.404), exercise habits (p=0.581), body mass index (p=0.898). Conclusion: The conclusion in this study is that there is a relationship between work posture, length of work, years of service, workload, age, and there is no relationship between gender, exercise habits, body mass index.